Is new energy driven by crude oil, high-tech sector or low-carbon notion? New evidence from high-frequency data. (1st September 2021) - Qu, Fang; Chen, Yufeng; Zheng, Biao
Abstract: There has been controversy over exactly what drives investment in new energy stocks. We contribute to this debate by exploring the volatility spillovers and its asymmetric effects between crude oil, new energy stocks, high-tech sector, and the low-carbon notion in China. This study is based on realized volatility, spillover index, and an improved spillover asymmetric measure method under high-frequency data. Empirical results reveal that only a few evidences back up the powerful volatility spillover from oil to new energy, which declares the crude oil should not be employed as a weathervane for the volatility of new energy. High-tech and low-carbon are main contributors to the volatility spillover of new energy, which shows China's new energy listed companies not only in the technical strength have been improved, but also in the concept of environmental protection has made the advance. Nevertheless, spillover asymmetric measure indicates, new energy, high-tech, and low-carbon are sensitive to positive news, which implies overemphasizing the role of new energy in technology and environmental protection may exacerbate the speculative mentality and potential financial bubbles of China's new energy stocks. Highlights: An extended spillover asymmetric measure method is employed to discuss the asymmetric effect of volatility spillovers. We use high-frequency data of the most representative index of China's financial market over 2011–2016. High-tech and low-carbon are the main contributors to the volatility spillover of new energy stocks. Crude oil should not be employed as a weathervane for the volatility of new energy stocks.